Enhanced osteogenic gene expressions and alkaline phosphatase activity of the composites based on bioactive glass and CuAl LDH for bone tissue engineering. (7th December 2022) - Bagherzadeh, Mojtaba; Aldhaher, Abdullah; Baheiraei, Nafiseh; Ahmadi, Sepideh; Rabiee, Navid
Abstract : A novel form of nanocomposite based on bioactive glass (BG) and CuAl LDH has been devised and manufactured for the first time in this paper. The produced nanocomposites, BG@CuAl LDH and BG@CuAl LDH@RO, were employed to examine the ability of the alkaline phosphatase activity to regulate the expression of COL 1, OCN and RUNX2 (ALP) gene expressions. The role of leaf extracts ( Rosmarinus officinalis [RO]) on enhanced osteogenic gene expression has been investigated. Also, the relative cell viability has been analyzed by MTT assay on the hBMSCs, HEK‐293 and PC12 cell lines after 24 and 48 hours of treatment. The results showed significantly increased gene expressions in different microenvironments, the presence and absence of ascorbic acid and low cytotoxicity towards different cell lines. In the case of the hBMSCs cell lines, the synthesized nanomaterials' cell attachment and proliferation findings proved completely successful. Abstract : Novel application of CuAl LDH‐based nanocomposite for bone tissue engineering